Impact of a reverse delta type add-on device on the flap-tip vortex of a wing - Altaf, Afaq; Tan, Boon Thong; Omar, Ashraf Ali; Asrar, Waqar (2016)
The effect of interactions of vortices produced by an outboard flap-tip of a half-span wing (NACA 23012 in landing configuration) and a slender reverse delta type add-on device, placed in the proximity of the outboard flap-tip, on the upper surface of the half-span wing is investigated using Particle Image Velocimetry in a closed loop low speed wind tunnel. Specifically the characteristics of the vortex interactions generated downstream in planes perpendicular to the free stream direction and their dependence on angles of attack at a chord-based Reynolds number of Rec=2.75×105 have been determined. It was found that the add-on device significantly reduces the tangential velocity magnitude and enlarges the vortex core of the resultant vortex by up to 36%. The aerodynamic performance of the half-span wing model was marginally affected by the use of a reverse delta type add-on device. The reduction in lift coefficient is 3.8% and the increase in drag coefficient is 14.9%.